2019
DOI: 10.1002/net.21887
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of transportation network cooperative games

Abstract: A basic question in network analysis concerns the quantification of the importance of each node in terms of network connectivity. To this end, a possible approach consists in using cooperative game theory tools to define a measure of node centrality. In this paper, given a transportation network, a cooperative game model with transferable utility (TU game) is considered. The nodes of the network represent the players in such a game, and the Shapley values of the nodes are used to measure centrality. The model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Then, the vector of the Shapley values of the players, represented therein by the network nodes, was used to evaluate the node centrality. Theoretical properties of the resulting centrality measure were investigated in [20,22]. Unfortunately, the utility functions defined in [22] are not suitable to model congestion, as they refer to situations in which the cost associated with each arc is given exogenously.…”
Section: Transportation Network Cooperative Gamesmentioning
confidence: 99%
“…Then, the vector of the Shapley values of the players, represented therein by the network nodes, was used to evaluate the node centrality. Theoretical properties of the resulting centrality measure were investigated in [20,22]. Unfortunately, the utility functions defined in [22] are not suitable to model congestion, as they refer to situations in which the cost associated with each arc is given exogenously.…”
Section: Transportation Network Cooperative Gamesmentioning
confidence: 99%
“…Indeed, vertex relevance measures from cooperative games were applied in several contexts in which the players were not necessarily modeled as rational/intelligent entities. For instance, the Shapley value was applied to investigate vertex relevance in gene regulatory networks [20] and transportation networks [10], [11], [12]. It was also proposed as a way to provide feature selection in machine-learning problems in which the players are features and the characteristic function measures the predictive power of each subset of features [21].…”
Section: Extensions Of the Theoretical Analysismentioning
confidence: 99%
“…Games restricted to graphs, first investigated in [8], are able to represent naturally occurring situations in which any two players from among a coalition of players can coordinate with each other only if they are joined by a path (i.e., by a channel of communication). Examples of studies in which graph-theoretical and game-theoretical tools are combined can be found in several recent works [9]- [11], with the aim to investigate vertex relevance in graphs. In our approach, we model the human body as a graph and apply game theory to measure in real time the most relevant joint of the body from which movement originates.…”
Section: Introductionmentioning
confidence: 99%
“…This work, which is in the same research direction as [16], studies Braess' paradox in the context of cooperative games with transferable utility on a graph [20], which can model, for example, transportation networks [6,8]. The players can be either nodes or arcs of the graph (in this paper, they are arcs).…”
mentioning
confidence: 99%